2023
DOI: 10.1002/cssc.202201901
|View full text |Cite
|
Sign up to set email alerts
|

Novel Sb−SnO2 Electrode with Ti3+ Self‐Doped Urchin‐Like Rutile TiO2 Nanoclusters as the Interlayer for the Effective Degradation of Dye Pollutants

Abstract: Stable and efficient SnO2 electrodes are very promising for effectively degrading refractory organic pollutants in wastewater treatment. In this regard, we firstly prepared Ti3+ self‐doped urchin‐like rutile TiO2 nanoclusters (TiO2‐xNCs) on a Ti mesh substrate by hydrothermal and electroreduction to serve as an interlayer for the deposition of Sb−SnO2. The TiO2‐xNCs/Sb−SnO2 anode exhibited a high oxygen evolution potential (2.63 V vs. SCE) and strong ⋅OH generation ability for the enhanced amount of absorbed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 95 publications
0
2
0
Order By: Relevance
“… 34 The removal rate constants of RhB and COD can be calculated as 0.0258 and 0.0027 min –1 , respectively. Compared with other electrodes ( Table S1 , Supporting Informations), the removal efficiencies and rate constants of RhB by Sb-doped SnO 2 /Ti electrode are higher than those by PbO 2 electrodes, 19 , 20 NiCo 2 O 4 electrode 25 and particle electrode, 27 but lower than those with BDD electrode, 15 TiO 2 nanoclusters/Sb-SnO 2 electrode, 22 porous Au electrode, 26 and CNTs/AG membrane on ITO electrode. 28 In this work, we degraded RhB in alkaline medium; however, other studies degraded RhB usually in a neutral or acidic medium, and the removal efficiency of RhB in alkaline medium involved in these studies is lower than that of our work.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“… 34 The removal rate constants of RhB and COD can be calculated as 0.0258 and 0.0027 min –1 , respectively. Compared with other electrodes ( Table S1 , Supporting Informations), the removal efficiencies and rate constants of RhB by Sb-doped SnO 2 /Ti electrode are higher than those by PbO 2 electrodes, 19 , 20 NiCo 2 O 4 electrode 25 and particle electrode, 27 but lower than those with BDD electrode, 15 TiO 2 nanoclusters/Sb-SnO 2 electrode, 22 porous Au electrode, 26 and CNTs/AG membrane on ITO electrode. 28 In this work, we degraded RhB in alkaline medium; however, other studies degraded RhB usually in a neutral or acidic medium, and the removal efficiency of RhB in alkaline medium involved in these studies is lower than that of our work.…”
Section: Resultsmentioning
confidence: 87%
“…As a typical organic dye, Rhodamine B (RhB) can color the water even at very low concentrations (approximately 1.0 mg·L –1 ), thus hindering the photosynthetic processes of aquatic organisms . Moreover, RhB has been found to have potential carcinogenicity, teratogenicity, and mutagenicity, and is difficult to degrade in the natural environment. In recent years, many studies have used RhB as the representative pollutant to investigate the treatment of organic dyes in wastewater and various anodes have been developed by boron-doped diamond (BDD), dimensionally stable anodes (DSA), , PbO 2 , SnO 2 , , and several new materials. In these studies, the effectiveness of electro-oxidation for the degradation of RhB has been proven, but it should be noted that these electrocatalytic oxidation processes usually run under neutral or weakly acidic conditions and the degradation performance of RhB in alkaline medium is not satisfactory. Liu et al reported that the removal efficiency of RhB was only 10% at the initial pH of 9, which is significantly lower than 96% in acid medium (pH 3) using the carbon nanotubes (CNTs)/agarose (AG) membrane on the ITO (indium tin oxide) electrode.…”
Section: Introductionmentioning
confidence: 99%